ANALISIS KUALITAS PELAYANAN PENDIDIKAN DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) BERBASIS WEB - Sri Haryati (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
Students are internal academic and administrative customers in a higher education environment. It is hoped that students as consumers can enjoy good educational services. However, it is necessary to have a forum for channeling the aspirations of student satisfaction levels as a benchmark for higher education performance in providing quality educational services. The focus of this study is the measurement of service satisfaction to students. This study uses the SERVQUAL instrument to measure student satisfaction and data analysis is carried out using the importance performance analysis (IPA) method and testing by creating a web-based questionnaire system design in which the hope is that this system can support university decision making, especially in the Computerized Accounting Study Program, Banjarmasin State Polytechnic Keywords : Education Services, Importance Performance Analysis (IPA), web-based.